PRESENTATION ON THE STRUCTURE OF PERM REGION AS PART OF REGIONAL IDENTITY - Podvintsev, O.B. (Perm Federal Research Centre Journal, 2016)
The article is devoted to the presentation and performance features of the territorial structure of the Perm region, Perm regional carriers peculiar identity, its historical and geographical reasons.